Numerical Algorithms for the Analysis of Initial Configuration in a Railway Catenary Structure and Its Code Implementation: A Software Tool CALPE - Tendero, Pedro; Rojo, Tomás; Cuartero, Fernando; Benet, Jesús; Arias, Enrique (Mathematical problems in engineering, 2015)
To obtain the best operating conditions in a railwayinfrastructure, as the pantograph/catenary system, is a priorityissue in modern railways, for a correct management and thebest performance of this infrastructure. Although most of thepublished works on this subject are oriented to solving dynamicproblems, in order to successfully address these problems a previousstatic study is necessary. In this paper, we present a methodologyfor the study of the forces in a railway catenary, according to theequations of statics equilibrium. The results of this work haveallowed us to develop two iterative algorithms that calculate asimple and computationally effective lengths of the droppers, whichis crucial to determine the initial structural configuration of thecatenary parameter. The obtained results have led us to theimplementation of a tool to obtain very precise assemblies withsignificant savings in maintenance, therefore still being used byADIF, the Spanish railway administration of railwaysinfrastructures.